The predictive role of social isolation in COVID-19 anxiety among older adults - Bahrami Mahdie; Marzieh Khatooni; Mojtaba Senmar; Hosseinali Movahedeh; Fateme Zarei; Seyedeh Ameneh Motalebi; Mohammad Amerzadeh (BMC Geriatrics)
Abstract Background COVID-19 is one of the most significant diseases that has spread in the present century. Older adults have been greatly affected by the negative consequences of the COVID-19 pandemic. Social isolation is one of the challenges of modern aging that leads to various detrimental conditions for health. Therefore, this study aimed to determine the predictive role of social isolation in COVID-19 anxiety among older adults. Methods This cross-sectional study with a descriptive-analytical approach was conducted in 2023. A total of 300 older adults were included in the study through cluster sampling from three districts in Qazvin City, Iran based on inclusion criteria. Data collection involved demographic information questionnaires, the COVID-19 Anxiety Questionnaire, and the Social Isolation Questionnaire. Data analysis was performed using descriptive tests and multivariate regression analysis with the SPSS 23 software. Results The mean and standard deviation of COVID-19 anxiety and social isolation among the participants were 10.99 and 28.10, respectively. The results of the multivariable regression model indicated that marital status (P = 0.04, β = 0.14), COVID-19-related deaths in the family (P = 0.02, β = 0.14), and social isolation (P = 0.03, β=-0.13) were associated with COVID-19 anxiety among older adults. Conclusion The findings of this study indicated that social isolation can predict COVID-19 anxiety in older adults. It is expected that policymakers and family members of older adults will take steps to enhance community-oriented approaches, such as group meetings and face-to-face visits, while adhering to the relevant health protocols.